Análisis de los Contenidos de Química del primer año de Bachillerato para Determinar la Secuencia Didáctica en la Unidad Educativa Riobamba, Periodo 2015-2016 - Rodríguez Camino, Mónica Consuelo (2017)
The research project was carried out in an educational institution called “Riobamba”, during the pre-teaching service of first year students of bachillerato in the area of Chemistry, evidencing a low performance in students who reach a an overall score of 6.75 (close to reach the required level of learning), the causes of this problem were considered: To teach science the educator has used the text prepared by the ministry of education , which analyzes issues that are not properly organized as they are fragmented i.e. it does not clearly explain a logical didactic sequence that must be applied , in addition the educator considers that students learning is minimum , because there is a lot of theory, leaving aside the practice . Therefore, this project aims to analyze the contents of chemistry and its relationship with the didactic sequence used by teachers in the first year of bachillerato in order to obtain better learning in students. In this research the following methodology was applied, the non-experimental design, type of study carried out is descriptive, explanatory, diagnostic and field, based on the inductive, deductive analytical and synthetic methods. The population consisted of students and teachers of chemistry of first year of bachillerato in the “Riobamba “school a sample was selected form students in room “E” using intentional non-probabilistic the questionnaire With the purpose of analyzing the data , concluding that the didactic sequence constitutes a contribution to the teaching work to facilitate the cognitive development of the student